2021
DOI: 10.1017/s0007485321000766
|View full text |Cite
|
Sign up to set email alerts
|

Ovigeny strategy of the parasitic wasp Cosmocomoidea annulicornis (Hymenoptera: Mymaridae): effect of female age, feeding and host availability on reproductive traits

Abstract: The reproductive traits of the mymarid wasp Cosmocomoidea annulicornis (Ogloblin) (Hymenoptera: Mymaridae) attacking eggs of the sharpshooter Tapajosa rubromarginata (Signoret) (Hemiptera: Cicadellidae) were evaluated under laboratory conditions. Bioassays were carried out to estimate the realized fecundity and egg load of females. The ovigeny index was calculated and different biological traits, such as body size, oöcyte length, gaster length and wing length, were analysed to assess significant associations b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 57 publications
0
2
0
Order By: Relevance
“…In addition, most of the available information is for experimental designs where females received an excess of hosts. For example, Manzano et al [68] reported that the egg production rate of Cosmocomoidea annulicornis (Ogloblin) (Hymenoptera: Mymaridae) females is affected by age. The lowest egg load observed is when the females are 1 and 12 hours old and the highest when females are 4, 5, and 8 hours old.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, most of the available information is for experimental designs where females received an excess of hosts. For example, Manzano et al [68] reported that the egg production rate of Cosmocomoidea annulicornis (Ogloblin) (Hymenoptera: Mymaridae) females is affected by age. The lowest egg load observed is when the females are 1 and 12 hours old and the highest when females are 4, 5, and 8 hours old.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, most of the available information is for experimental designs where females received an excess of hosts. For example, Manzano et al [78] reported that the egg production rate of Cosmocomoidea annulicornis (Ogloblin) (Hymenoptera: Mymaridae) females is affected by age. The lowest egg load observed is when the females are 1 and 12 days old and the highest when females are 4, 5, and 8 days old [79].…”
Section: Plos Onementioning
confidence: 99%